Quercetin and catechin synergistically inhibit angiotensin II-induced redox-dependent signalling pathways in vascular smooth muscle cells from hypertensive rats - Redondo, Analia Lourdes (2012)
Dietary flavonoids, present in different amount in foods, are associated with the prevention of hypertension, but little is known about the interactions between them. The aim of this study was to explore the effect of quercetin (Q), catechin (C) and the mixture, on Angiotensin II (AngII)-induced redox-dependent signalling pathways and cell behaviour. Mesenteric smooth muscle cells (MesSMC) from spontaneously hypertensive rats (SHR) were incubated with AngII (0.1 μmol/L) alone, or with the mixture of low concentrations of Q and C. AngII-increased ROS production was reduced by the mixture of separately ineffective low concentration of Q (15 μmol/L) plus C (20 μmol/L). This mixture reduced AngII-stimulated NAD(P)H oxidase activation and p47phox translocation to the cell membrane, without affecting Nox2 expression. Co-incubation of Q + C significantly inhibited AngII-induced migration and proliferation, and these effects were independent of p-ERK1/2 and related with reduced p38MAPK phosphorylation. These findings demonstrated that low concentrations of singly non-effective flavonoids when are combined exert a synergistic effect in inhibiting AngII-induced redox-sensitive signalling pathways.